Speaking Problems and Learning Strategy: Investigation EFL Use of University in Indonesia - Munawir, Ahmad; Rahman, Wiwiek Zulfiana; Kafrawi, Muhammad; Satriani, Satriani; Marya A, Marya A (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
This study aims to identify the speaking issues second semester English education students at the Islamic Institute of Religion (IAI) As' Adiyah Sengkang encountered that prevented students from speaking English and the solutions employed by English education students to address those issues. In the second semester of the Islamic Institute (IAI) As'adiyah Sengkang, 12 English education students participated in a qualitative study that includes this research. Interviews, questionnaires, and observation served as the research tools. The findings indicated that the second-semester English education students' speaking issues were due to a lack of vocabulary mastery, a lack of confidence, pronunciation issues, feelings of embarrassment and fear of making mistakes, nervousness, and a habit of speaking in their native tongue. Students in the second semester of English education employ the following methods to improve their speaking abilities: learning English through songs and movies, practicing a lot, and remaining calm.